The literatures of the Philippines - Lacia, Ferdilyn C.; Libunao, Lydia L.; Fabella, Mark G.; Buhain, Vivian I. (Rex Book Store, 2015)
The Literatures of the Philippines is prepared for Philippine Literature courses as mandated by the Commission on Higher Education (CHED) in CMO No.59, Series of 1996, which is aimed at updating the General Education Curriculum to make the same more responsive to the demands of the next millenium.